2019
DOI: 10.1002/nur.21936
|View full text |Cite
|
Sign up to set email alerts
|

Measuring exercise self‐efficacy in Hong Kong Chinese adults with cardiovascular risk: Validation of a Chinese version of the Cardiac Exercise Self‐efficacy Instrument

Abstract: About one-third of adults are physically inactive and thus prone to cardiovascular diseases. While self-efficacy mediates health behavior, its influences on exercise behavior among Chinese is yet to be explored by a validated instrument. This study aimed to examine the psychometric properties of the Hong Kong Chinese version of the Cardiac Exercise Self-efficacy Instrument (CESEI-C), which had been translated previously by these authors. The psychometric properties of the CESEI-C were tested with 160 Hong Kong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…General self‐efficacy expresses the belief of a person in their ability to meet their difficulties, and self‐efficacy instruments particular to the disease include a more specific evaluation. As many instruments assessing general self‐efficacy and disease‐specific self‐efficacy, there are also behaviour‐specific self‐efficacy instruments on healthy eating, 28‐31 physical activity 22,32‐36 and medication adherence 37‐39 . For a complete assessment of the self‐efficacy, it is necessary to use different behaviour‐specific self‐efficacy instruments.…”
Section: Introductionmentioning
confidence: 99%
“…General self‐efficacy expresses the belief of a person in their ability to meet their difficulties, and self‐efficacy instruments particular to the disease include a more specific evaluation. As many instruments assessing general self‐efficacy and disease‐specific self‐efficacy, there are also behaviour‐specific self‐efficacy instruments on healthy eating, 28‐31 physical activity 22,32‐36 and medication adherence 37‐39 . For a complete assessment of the self‐efficacy, it is necessary to use different behaviour‐specific self‐efficacy instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Self-efficacy- Five items from Exercises Self-Efficacy Chinese Version [ 23 ], with good validity of construct (Cronbach alpha at 0.7) [ 24 ] were adopted to measure older adults’ exercise self-efficacy change during COVID-19. The items included: their perceptions of having the confidence to attain their physical activity and exercise goals; being physically active when tired; exercising without social support; and motivating themselves to begin physical activity again after a long time.…”
Section: Methodsmentioning
confidence: 99%
“…The total score of C‐CESEI ranges from 16 to 80, with a higher score denoting a higher level of self‐efficacy in performing the exercise. This instrument has good internal consistency with Cronbach's alpha of 0.91 (Cheng et al, 2019). In our study, the Cronbach's alpha coefficient of C‐CESEI was 0.83.…”
Section: Methodsmentioning
confidence: 99%
“…Self-efficacy, the belief in one's ability to perform behaviours needed to manage prospective events (Bandura et al, 1999), is an important determinant of behavioural change. Previous studies showed that a high level of exercise self-efficacy was associated with increased PA amount, as well as exercise capacity among people with cardiovascular risk (Cheng et al, 2019). On the other hand, a recent systematic review showed that intrinsic motivation, as purported in the self-determination theory (Ryan & Deci, 2000), was associated with the maintenance of performing adequate physical activity (PA) among adults (Rodrigues et al, 2018).…”
mentioning
confidence: 99%